Greece on air : engagements with Ancient Greece on BBC Radio, 1920s-1960s - Wrigley, Amanda (Classical presences, 2016)
'Greece on Air' offers a substantial discussion of the fascinating history of creative and public engagements with ancient Greek literature, history, and thoughts via the BBC Radio, from the birth of domestic broadcasting in the 1920s up to the 1960s